Quality of Information about Accelerated Orthodontics on Instagram - Buyuk Suleyman Kutalmış; Imamoglu Tugce; Yavuz Mustafa Cihan (Balkan Stomatological Society, 2021)
Background/Aim: Social media has become popular in recent years in dentistry. This study aims to evaluate the posts shared on Instagram related to accelerated orthodontic treatment.